Workshop pembuatan media pembelajaran Lumio dan Wordwall bagi Guru SDN 03 Makamhaji, Sukoharjo - Kaltsum, Honest Ummi; Wulandari, Alfiah Sri Murni; Fadillah, Retno; Fauzy, Ibrahim; Khotimah, Nur Ahlul; Ayu, Dinda Puspita; Mahya, Yogi Muthohir Zuhad; Qonita, Farra Risti (Tintamas: Jurnal Pengabdian Indonesia Emas, 2024)
This service aims to improve the understanding and skills of State Elementary School (SDN) 03 Makamhaji teachers in utilizing artificial intelligence (AI) and augmented reality (AR) technology in the learning process. The program presented is implemented through education, training and workshops on using Lumio and Wordwall learning media. The approach covers various activities, including coordination, implementation of activities, data collection, reporting, monitoring and return visits. The methods used include lectures, tutorials, simulations, and question-and-answer sessions to ensure maximum effectiveness and interaction from participants. The evaluation shows that SDN 03 Makamhaji teachers are starting to use the Lumio and Wordwall applications, even though there are still technical obstacles and students' readiness to face digital learning. The use of these applications is not yet fully integrated into the learning process but provides variety and increases student involvement.